2012
DOI: 10.1021/es203465x
|View full text |Cite
|
Sign up to set email alerts
|

Methane Emissions from a Small Wind Shielded Lake Determined by Eddy Covariance, Flux Chambers, Anchored Funnels, and Boundary Model Calculations: A Comparison

Abstract: Lakes are large sources of methane, held to be responsible for 18% of the radiative forcing, to the atmosphere. Periods of lake overturn (during fall/winter) are short and therefore difficult to capture with field campaigns but potentially one of the most important periods for methane emissions. We studied methane emissions using four different methods, including eddy covariance measurements, floating chambers, anchored funnels, and boundary model calculations. Whereas the first three methods agreed rather wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
156
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(167 citation statements)
references
References 34 publications
8
156
3
Order By: Relevance
“…Monitoring and characterization of CH 4 and CO 2 fluxes in representative reservoirs of different power densities, locations and time since construction are critically needed to better quantify the total GHG emissions from the hydroelectric reservoirs in China. Although various sampling and analysis techniques have been used, measurement of GHG emissions from reservoirs -which can cover several hundreds of square kilometres and have depths exceeding 100 m -is a complicated process 30,31 . The limited number of sampling spots may not be able to represent the overall emissions from the reservoirs with complex hydrodynamics 23,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring and characterization of CH 4 and CO 2 fluxes in representative reservoirs of different power densities, locations and time since construction are critically needed to better quantify the total GHG emissions from the hydroelectric reservoirs in China. Although various sampling and analysis techniques have been used, measurement of GHG emissions from reservoirs -which can cover several hundreds of square kilometres and have depths exceeding 100 m -is a complicated process 30,31 . The limited number of sampling spots may not be able to represent the overall emissions from the reservoirs with complex hydrodynamics 23,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Chambers and the EC methods are in relatively good agreement in these studies, and the discrepancy still observed is mainly due to spatial heterogeneity of the gas flux. Comparisons over water bodies are sparse (Eugster et al, 2011;Schubert et al, 2012), yet the results, only for CH 4 flux, show that the methods are of the same order of magnitude. Since both methods are widely used, further parallel studies with more direct comparisons are needed.…”
Section: Introductionmentioning
confidence: 99%
“…During recent years EC measurements have been made also over lakes, mainly for CO 2 flux (e.g. Eugster et al, 2003;Huotari et al, 2011;Jonsson et al, 2008;Vesala et al, 2006) but in a few cases also for CH 4 flux (Eugster et al, 2011;Sahlée et al, 2014;Schubert et al, 2012). The EC method yields continuous measurements with limited labour, but requires expensive instrumentations and extensive data post-processing.…”
Section: Introductionmentioning
confidence: 99%
“…Because current upscaling estimates are based on these methods, comparison is needed to reduce the uncertainties in current estimates of the role of freshwaters in global carbon cycle. Such a comparison also gives valuable information on measurement technique development needs, and so far there is only one comparative study including all three methods for CH 4 in a temperate lake (Schubert et al, 2012). This is, to our knowledge, the first study including the three measurement methods for both CH 4 and CO 2 in a boreal lake, even though the boreal zone harbours a large fraction of the global lakes (Lehner and Döll, 2004;Verpoorter et al, 2014).…”
mentioning
confidence: 95%
“…According to recent studies, this upscaling approach strongly underestimates current emissions from lakes and improved methods are needed (e.g. Schubert et al, 2012;Mammarella et al, 2015). Heiskanen et al (2014) and Tedford et al (2014) suggest k models based also on heat flux and water turbulence measurements for more accurate estimates.…”
mentioning
confidence: 99%